Rumors: Its Concept and Its Danger. Its Ruling and Ways to Prevent It from An Islamic Point of View - Raqeb Saeed Sharaf; Shukur Mahmud Abdullah (QALAAI ZANIST JOURNAL, 2022)
This research, tagged with (Rumors, their concept and danger. their ruling and methods of prevention from then. From an Islamic perspective). It is known that rumor is one of the phenomena that all human societies have known since ancient times. Undermining them, fanning the fire of strife or wars. The rumor has passed through several stages, and developed with the development of ages and the diversity of media, and the golden age of rumor began with the technical development and the flourishing and diversification of psychological warfare means and the development of its methods during the First World Wars (1914 AD - 1918 AD) and World War II (1939 AD - 1945 AD) and it continued until it reached Our current era, through the technological revolution and the development of modern media and communication, which are increasing in diversity and expansion day by day, and the importance of rumors, but rather their danger, lies in the fact that they interfere in all political, social, economic, cultural and military aspects at the local and global levels, and they spread rapidly, especially in times of crisis. Of its various kinds, whether crises on the political, economic or social level, and rumor has a major role in influencing and directing people's lives, and it is at the forefront of the factors shaping and directing public opinion. Prevention and fight against rumor.